Faktor determinan dan disparitas kesehatan gigi dan mulut anak di wilayah perkotaan dan perdesaan: A systematic review - Razin Alifahrezy Setyaliani; Dwi Sarwani Sri Rejeki; Suratman Suratman (Holistik Jurnal Kesehatan, 2026)
Background: Oral health problems during childhood can have long-term impacts on oral health in adulthood, negatively impacting children's general health and academic achievement. Furthermore, children's oral health is influenced by various determinants and shows differences between urban and rural areas. Purpose: To analyze the determinants and disparities in oral health among children in urban and rural areas. Method: This systematic review used the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to analyze and evaluate research findings identified through a literature search in PubMed and Google Scholar using the keywords "oral health" AND "children" AND "rural" AND "urban" AND "differences." Results: There were differences in the burden of untreated oral disease and lower access to health information among children in rural areas compared to urban areas. Conclusion: Disparities in oral health among children exist between rural and urban areas, influenced by various social, economic, behavioral, and access to health services factors. Children in rural areas tend to be at higher risk of oral health problems due to limited access to services, low health literacy, and uneven distribution of dental health professionals. Suggestion: Promotive and preventive interventions are needed to improve parental knowledge and behavior and ensure equitable access to dental health services, especially in rural areas. Furthermore, research should encompass a wider range of regions and variables, including research in Indonesia, to obtain a more comprehensive and contextualized picture of the determinants and disparities in children's oral health.   Keywords: Determinants; Health Disparities; Oral Health; Rural Areas; Urban Areas.